Seismic performance of concentrically braced frames with and without brace buckling. (15th June 2017) - Shen, Jay; Seker, Onur; Akbas, Bulent; Seker, Pinar; Momenzadeh, Seyedbabak; Faytarouni, Mahmoud
Highlights: Braces in SCBFs often fracture prior to 2% story drift ratio response. Columns in the SCBF are subjected to large flexural demand over capacity ratio. Beams yield in two-story X-braced frames, increasing brace ductility demand. Buckling-controlled brace frame is an efficient seismic force resisting structure. Abstract: This paper presents an analytical study on seismic performance of special concentrically braced frames (SCBFs) with and without brace buckling. It demonstrates that the collapse prevention goal needs attention in modern buildings using SCBFs as main seismic-force-resisting systems, and an simple and low-cost solution is possible to achieve this goal. Typical 6-story buildings using two-story X-braced frames with strong and weak braced-intersected beams and inverted V braced frames with and without brace buckling were subjected to a set of 15 earthquake ground motions, and resulting seismic responses were discussed in terms of seismic strength and deformation demands on braces, beams and columns. The study finds that the braces in SCBFs often fracture prior to 2% story drift ratio response, particularly in the popular two-story X-braced frames with weak beams, mainly due to premature yielding of the beams. The buckling-controlled braced frames (BCBFs) are shown to be a cost-effective system to improve the seismic performance of SCBFs. The analysis indicates that the buckling-controlled braces may substantially reduce story drift response, eliminate weak beam yielding, and prevent braces from fracturing.